Concept and Implementation of Tarbawi Knowledge and Interpretation in Islamic Education - Nia Kurnia; Hafid; Cecep Anwar; Yuni Purnamasari; Jaka Nugraha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Islamic education has a very important role in shaping the character and morals of students. The concept of knowledge in Islam does not only include worldly knowledge, but is also closely related to spiritual and moral values. One relevant approach to integrating these values in the educational process is tafsir tarbawi, which uses the Al-Qur'an as the main source of values in education. This research aims to explore the concept of knowledge in Islamic education and the implementation of tarbawi interpretation in the context of modern education. The methodology used in this research is a qualitative approach with in-depth literature study as well as interviews with several educators and managers of Islamic educational institutions who apply tarbawi interpretation. This research also analyzes various learning programs and curricula that integrate Islamic values in the educational process. The research results show that the application of tarbawi interpretation can increase the understanding and application of Islamic values in students' lives. Through thematic discussions that connect the verses of the Qur'an with learning themes, students not only learn academic knowledge but also imbibe moral and spiritual values. Despite this, the implementation of tafsir tarbawi faces several obstacles, such as the limited understanding of teachers about this method and the lack of continuous training. This research recommends continuous teacher training, more holistic curriculum development, as well as value-based evaluation to improve the quality of Islamic education more comprehensively.